2004
DOI: 10.1177/0363546503259616
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Histological Evaluation of Osteochondral Transplantation in a Rabbit Model

Abstract: Osteochondral transplantation may be a viable treatment option; however, long-term investigation on graft function is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 31 publications
4
75
0
8
Order By: Relevance
“…Standard defects were created at a depth of 4 mm and a diameter of 4 mm with a standard disposable osteochondral autograft transport system (DePuy, Warsaw, IN), and the rest of the process was performed as suggested by Nam et al [20]. For all experiments, the right knee was the test and the left knee was the control.…”
Section: Methodsmentioning
confidence: 99%
“…Standard defects were created at a depth of 4 mm and a diameter of 4 mm with a standard disposable osteochondral autograft transport system (DePuy, Warsaw, IN), and the rest of the process was performed as suggested by Nam et al [20]. For all experiments, the right knee was the test and the left knee was the control.…”
Section: Methodsmentioning
confidence: 99%
“…In the transplanted osteochondral graft, stiffness might be temporarily decreased in the postoperative course [15,28]. We previously reported decreased stiffness at postoperative weeks 1, 3 and 8 compared to normal cartilage stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Histological analysis of transplanted osteochondral grafts indicates that, in an optimal autologous osteochondral transplantation, osteochondral grafts are incorporated into the defect, thereby, retaining the integrity of hyaline cartilage and cancellous bone, and maintaining the congruity of the articular surface in weight-bearing areas [5,13]. In contrast, changes in the mechanical properties of the transplanted osteochondral graft have been analysed in various autologous osteochondral transplantation models and evaluated at various periods after surgery [9,10,15,28]. We previously demonstrated that the structural properties of an osteochondral cylinder-graftrecipient construct immediately after surgery are not significantly different from those of normal cartilage and that the structural properties of an osteochondral cylindergraft-recipient reconstruction are significantly worse at postoperative weeks 1 through 8 than in normal cartilage [14].…”
Section: Introductionmentioning
confidence: 99%
“…23 In multiple studies including rabbit, ovine, and porcine models, chondrocytes and osteocytes of the osteochondral graft have been shown to survive transplantation. [24][25][26][27][28][29][30] Osteochondral grafting has also been used in the capitellum, talus, and femoral head, with graft viability proven with second-look arthroscopy, MRI, and biopsy. [31][32][33][34][35][36][37] The MRI of our patient at 21 months postoperative showed bone incorporation of the graft to the capitate and the presence of graft cartilage (►Fig.…”
Section: Discussionmentioning
confidence: 99%